Actor Collaboration in Community Empowerment During the COVID-19 Pandemic Jelgung Village, Sampang Regency - Hidayat, Endik; Baihaqi, Aufa Izzudin; Marta, Rustono Farady (WARTA LPM, 2022)
This article discusses the model of community empowerment during the COVID-19 pandemic in Jelgung village. As for the two questions that arise, what is the model of community empowerment and the actors involved of the Jelgung village government during the pandemic? The theory used is the theory of social empowerment related to the actors involved in the program. By using qualitative methods and a case study approach at the village level. Two data models in this study are primary data and secondary data. Primary data collection by interview and focus group discussion (FGD), the informants consist of village heads, village officials and community leaders. The results showed that empowerment in Jelgung village was driven by two main actors, namely individuals from community leaders and local and village governments. While empowerment activities are divided into two forms, namely labor intensive including training and capital intensive covering small and medium business capital.